2022
DOI: 10.3390/ijms23126565
|View full text |Cite
|
Sign up to set email alerts
|

Functional Allele Validation by Gene Editing to Leverage the Wealth of Genetic Resources for Crop Improvement

Abstract: Advances in molecular technologies over the past few decades, such as high-throughput DNA marker genotyping, have provided more powerful plant breeding approaches, including marker-assisted selection and genomic selection. At the same time, massive investments in plant genetics and genomics, led by whole genome sequencing, have led to greater knowledge of genes and genetic pathways across plant genomes. However, there remains a gap between approaches focused on forward genetics, which start with a phenotype to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 216 publications
0
7
0
Order By: Relevance
“…The selected candidate genes identified in our study can be further confirmed using the two accessions and several other accessions with contrasting AG phenotypes via reverse transcription polymerase chain reaction and other genomic tools. Moreover, functional validation can be performed using transgenic studies including knocking out each candidate gene in the tolerant genotype with gene editing (Thomson et al., 2022). Furthermore, these findings will help in designing markers to be used in marker‐assisted breeding programs for rice improvement against flooding during germination stress (Gonzaga et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The selected candidate genes identified in our study can be further confirmed using the two accessions and several other accessions with contrasting AG phenotypes via reverse transcription polymerase chain reaction and other genomic tools. Moreover, functional validation can be performed using transgenic studies including knocking out each candidate gene in the tolerant genotype with gene editing (Thomson et al., 2022). Furthermore, these findings will help in designing markers to be used in marker‐assisted breeding programs for rice improvement against flooding during germination stress (Gonzaga et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Protoplasts have been used for the testing of CRISPR/Cas9 constructs and sgRNA activity in a diverse range of species, including legumes such as peanut and chickpea, but a protocol has not yet been developed for cowpea [22][23][24]. Likewise, Agroinfiltration of leaves has also been used with the CRISPR-Cas9 system for sgRNA validation and gene expression assays [25][26][27]. The current study aims to knock out the cowpea phytoene desaturase (PDS) gene using a CRISPR-Cas9 construct designed with four multiplexed sgRNAs through PEG transformation in cowpea protoplasts and agroinfiltration in cowpea leaves.…”
Section: Introductionmentioning
confidence: 99%
“…Plants 2023, 12, 3564 2 of 14 Subsequently, a list of candidate genes is refined, and functional validation is performed through complementation and/or genome editing [12]. Recent advances in genome editing techniques have begun to greatly accelerate progress in the genetic dissection of key traits in plants but have not yet been thoroughly optimized for crop improvement [13].…”
Section: Introductionmentioning
confidence: 99%
“…The identification of causal genes controlling key traits in crop species often begins with quantitative trait locus (QTL) mapping and genome-wide association studies (GWASs). Subsequently, a list of candidate genes is refined, and functional validation is performed through complementation and/or genome editing [12]. Recent advances in genome editing techniques have begun to greatly accelerate progress in the genetic dissection of key traits in plants but have not yet been thoroughly optimized for crop improvement [13].…”
Section: Introductionmentioning
confidence: 99%